Core components of infection prevention and control programs at the facility level in Kazakhstan: key challenges and opportunities - Anna Deryabina; Ainur Aiypkhanova; Almat Juvashev; Kuanysh Alimbetov; Kanat Tekebayev; Getachew Kassa; Andrea A. Howard (Antimicrobial Resistance and Infection Control, 2023)
Abstract Background Kazakhstan is developing a National Roadmap to strengthen its Infection Prevention and Control (IPC), but until recently has lacked a country-wide facility-level assessment of IPC performance gaps. Methods In 2021, the World Health Organization (WHO)’s IPC Core Components and Minimal Requirements were assessed at 78 randomly selected hospitals across 17 administrative regions using adapted WHO tools. The study included site assessments, followed by structured interviews with 320 hospital staff, validation observations of IPC practices, and document reviews. Results All hospitals had at least one dedicated IPC staff member, 76% had IPC staff with any formal IPC training; 95% established an IPC committee and 54% had an annual IPC workplan; 92% had any IPC guidelines; 55% conducted any IPC monitoring in the past 12 months and shared the results with facility staff, but only 9% used monitoring data for improvements; 93% had access to a microbiological laboratory for HAI surveillance, but HAI surveillance with standardized definitions and systematic data collection was conducted in only one hospital. Adequate bed spacing of at least 1 m in all wards was maintained in 35% of hospitals; soap and paper towels were available at the hand hygiene stations in 62% and 38% of hospitals, respectively. Conclusions Existing IPC programs, infrastructure, IPC staffing, workload and supplies present within hospitals in Kazakhstan allow for implementation of effective IPC. Development and dissemination of IPC guidelines based on the recommended WHO IPC core components, improved IPC training system, and implementation of systematic monitoring of IPC practices will be important first steps towards implementing targeted IPC improvement plans in facilities.